Congenital heart defects and clinical and anamnestic determinants of gestation complications - Nakonechnyi, S. Yu.; Sokolovska, I. S.; Наконечний, Сергій Юрійович; Соколовська, Ірина Сергіївна (My University, 2023)
Pregnant women with low- and moderate-risk congenital heart defects have a statistically significantly higher number of comorbid somatic pathologies (urinary tract diseases, thyroid diseases and disorders of the autonomic nervous system), and are also more likely to report tobacco smoking both before pregnancy and during gestation. Patients with low- and moderate-risk congenital heart defects are statistically significantly more likely than pregnant women in the control group and women with high maternal risk congenital heart defects to terminate a previous pregnancy by induced surgical abortion and have a higher rate of delivery by cesarean section in the past.